Creativitatea în spațiul unor servicii educaționale - Moldoveanu, Maria (Calitatea Vieții, 1993)
On the basis of the researches referring to creativity as a dimension of the quality of life, this study pleads for the decisive role of the school, of the educational system generally speaking in the development of the creative features.